MODIFIKASI TEPUNG LABU KUNING (Cucurbita Flour) DENGAN HIDROLISIS SECARA ENZIMATIS - Yeni Sulastri; Syirril Ihromi; Nurhayati Nurhayati (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2016)
Yellow pumpkin (Cucurbita moschata) could potentially be used as a source of modified flour material to to reduce the consumption of wheat. One method of modified flour that can be done is the enzymatic hydrolysis process using α-amylase enzyme. This research used α-amylase enzyme of small green pea sprout. Objective of this research is to obtained the best condition incubation periode and addition small green pea sprout. The experimental design of the research employed completely randomized design with two factors, incubation periode with 3 levels of treatment (24, 48, and 72 hours) and addition small green pea sprout (10%, 20%, and 30% (b/b dry flour)). The incubation periode was significantly take affect at level significance 95% to solubility and swelling power but not significantly take affect to water absorbing capacity (WAC), oil absorbing capacity (OAC), and β-caroten content. Addition small green pea sprout was significantly take affect at level significance 95% to solubility and swelling power but not significantly take affect to water absorbing capacity (WAC) and oil absorbing capacity (OAC). In addition, the study confirmed that the incubation periode of 48 hours and small green pea sprout of 30% b/b dry flour were the best condition possible. The results at this condition solubility of 61.45%, swelling power of 31.86%, WAC of 3.04 (g), OAC of 2.62 (g/g), and β-caroten content of 3.08 mg/100 g. Keywords: incubation periode, modified yellow pumpkin flour, small green pea sprout ABSTRAK Labu kuning merupakan salah satu sumber pangan dan sumber pati potensial yang dapat dimanfaatkan sebagai bahan baku tepung termodifikasi untuk mengurangi konsumsi terigu. Salah satu metode modifikasi tepung yang dapat dilakukan adalah proses hidrolisis secara enzimatis dengan menggunakan enzim α-amilase. Tujuan penelitian ini adalah untuk menentukan kondisi terbaik lama inkubasi dan penambahan kecambah kacang hijau melalui proses hidrolisis secara enzimatis. Rancangan penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan dua faktor yaitu lama inkubasi dengan 3 taraf perlakuan yaitu 24, 48, dan 72 jam dan penambahan kecambah kacang hijau 10, 20, dan 30% dari bobot tepung labu kuning yang akan dimodifikasi. Hasil penelitian menunjukkan lama inkubasi berpengaruh nyata pada tingkat kepercayaan 95% terhadap kelarutan, swelling power, dan daya serap minyak namun tidak berpengaruh nyata terhadap daya serap air tepung labu kuning termodifikasi. Penambahan kecambah kacang hijau berpengaruh nyata terhadap kelarutan dan swelling power namun tidak berpengaruh nyata terhadap daya serap air dan daya serap minyak. Kondisi terbaik proses modifikasi pati labu kuning secara enzimatis adalah pada lama inkubasi 48 jam dan penambahan kecambah kacang hijau 30%. Pada kondisi ini dihasilkan kelarutan 61,45%, swelling power 31,86%, daya serap air 3,04 (g/g), daya serap minyak 2,62 (g/g), dan β-karoten 3,08 mg/100 g.